Postoperative pain after tonsillectomy – the value of standardized analgesic treatment protocols - Gostian, Antoniu Oreste; Loeser, Johannes; Tholen, Christian; Wolber, Philipp; Otte, Martin; Schwarz, David; Heindl, Ludwig Maximilian; Balk, Matthias; Gostian, Magdalena (Auris Nasus Larynx, 2020)
Objective: To alleviate pain after tonsillectomy (TE) with escalating gradual treatment protocols in a prospective trial. Materials & Methods: Following TE, 83 consecutive adult patients were treated with two different four-staged escalating analgesic protocols. Metamizole served as basic medication in protocol 1 (PT1; n = 44), whereas with protocol 2 (PT2; n = 39) ibuprofen was applied as baseline analgesic. Both protocols were escalated according to the patient´s needs to metamizole and ibuprofen vice versa and additional weak to strong opioids. The primary efficacy endpoint was defined as the minimum and maximum pain as well as pain on ambulation (NRS, 0–10). Secondary endpoints comprised analgesic score, patient satisfaction and treatment-related side-effects. Results: Both patient groups exhibited similar demographic characteristics (PT1: Ø 28.8 years; 64% ♀ and PT2: Ø 26.6 years; 56% ♀). Maximum pain (6.7 ± 1.9 vs. 7.6 ± 1.6, t(81) = −2.254, p = 0.027) and pain on ambulation (5.0 ± 1.8 vs. 5.8 ± 1.8, t(81) = -2.114, p = 0.038) were significantly higher with PT2. 68.2% of patients with PT1 needed an escalation of analgesic treatment compared to 100% with PT2 (p < 0.001). The opioid consumption was also significantly higher with PT2 (43.2% vs. 71.8%, p < 0.001). There were no significant differences regarding functional impairments, side-effects and patient satisfaction (7.0 ± 2.0 vs. 7.4 ± 2.4, t(79) = −0.897, p = 0.373). Conclusion: Both treatment protocols yielded in a high degree of patient satisfaction but dissatisfactory pain relief following TE. Metamizole can be recommended as a basic medication allowing for improved pain relief. Reported pain intensities were independent of the amount of opioid intake. Further research is mandatory to standardize and improve analgesic treatment after TE.
CRIS-Team Scopus Importer:2020-06-23
Keywords: Non-opioid; Opioid; Pain therapy; Postoperative pain; Quality management; QUIPS; Tonsillectomy